2008
DOI: 10.1158/1055-9965.epi-07-0686
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Axis and Oncogenic Human Papillomavirus Natural History

Abstract: High serum levels of insulin-like growth factor-I (IGF-I) are reported to be a risk factor for several common cancers, and recent cross-sectional data suggest a possible additional association of IGF-I with cervical neoplasia. To prospectively assess whether circulating IGF-I levels influence the natural history of oncogenic human papillomavirus (HPV), the viral cause of cervical cancer, we conducted a pilot investigation of 137 women who underwent semiannual typespecific HPV DNA PCR testing and cervical cytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Levels of IGF-I in young women may be inversely associated with high-grade cervical intraepithelial neoplasia, a precursor to cervical cancer (Schaffer et al, 2007). Our results showed strong association of IGFs with the HPV status in Indian patients with advanced cancer cervix and are in concordance with the findings of the previous studies (Mathur et al, 2003;Wu et al, 2003;Schaffer et al, 2007;Harris et al, 2008;Lee et al, 2010).…”
Section: Western Blot Analysis Of Igf-i Igf-ii Igfbp-iii and β-Acsupporting
confidence: 92%
See 3 more Smart Citations
“…Levels of IGF-I in young women may be inversely associated with high-grade cervical intraepithelial neoplasia, a precursor to cervical cancer (Schaffer et al, 2007). Our results showed strong association of IGFs with the HPV status in Indian patients with advanced cancer cervix and are in concordance with the findings of the previous studies (Mathur et al, 2003;Wu et al, 2003;Schaffer et al, 2007;Harris et al, 2008;Lee et al, 2010).…”
Section: Western Blot Analysis Of Igf-i Igf-ii Igfbp-iii and β-Acsupporting
confidence: 92%
“…It has been shown in animal models that circulating IGF-I levels may play a significant role in carcinogenesis (Shen et al, 2006). Some studies have suggested that serum levels of IGF-I, IGF-II or IGFBP-III may be useful biomarkers for assessing risk of SIL or cervical cancer development (Mathur et al, 2003;Wu et al, 2003;Schaffer et al, 2007;Harris et al, 2008;Lee et al, 2010). In this study, we have explored the expression of the IGF system in cervical cancer patients and evaluated its potential association with HPV status by analysing its circulatory and cellular expression.…”
Section: Molecular and Circulatory Expression Of Insulin Growth Factomentioning
confidence: 99%
See 2 more Smart Citations
“…A recent prospective study reported a possible influence of the IGF axis on the natural history of oncogenic HPV and the development of cervical neoplasia (Harris et al, 2008). A high IGF-I/IGFBP-3 ratio was associated with increased persistence of oncogenic HPV infection [adjusted hazard ratio (AHR), 0.14; 95% confidence interval (95% CI), 0.04-0.57], whereas IGFBP-3 was inversely associated with both the incident detection of oncogenic HPV (AHR, 0.35; 95%CI, 0.13-0.93) and the incidence of oncogenic HPV positive cervical neoplasia (that is, squamous intraepithelial lesions at risk of progression; AHR, 0.07; 95% CI, 0.01-0.66).…”
Section: Serum Levels Of Igfs As Cervical Cancer Biomarkersmentioning
confidence: 99%